A Case of Angiomyolipoma Arising in the Tongue. (8th November 2011) - Yura, Shinya; Terahata, Shintaro; Sugiguchi, Shun
Abstract : A 61-year-old woman was referred to our hospital with a mass in the left proglossis. The lesion was excised with a provisional diagnosis of hemangioma. The mass was well-demarcated and easily dissected with an ultrasonic surgical aspirator. The histopathologic diagnosis was angiomyolipoma arising in the tongue. There were no signs of recurrence at followup at 18 months.